Evaluasi bobot badan Sapi Bali (Bos sondaicus) pada masa qurban di Kabupaten Karangasem, Propinsi Bali - yuga suwarsa; Wahyu Suryadi Pranata; Ai Nurfaidah; Rizki Prasetiadi; Asep Rahmat Haerudin (Fakultas Pertanian Universitas Majalengka, 2025)
This study aimed to compare the body weight of Bali cattle weighed as qurban animals during Eid al-Adha 1445 H (2024 AD) and 1446 H (2025 AD) in Karangasem Regency, Bali Province. Body weight data were obtained from the weighing of 202 head of cattle in 1445 H and 223 head of cattle in 1446 H. Descriptive analysis was performed to determine the mean, standard deviation, and coefficient of variation (CV), while the comparison between years was conducted using the Mann–Whitney U test, since the data were not normally distributed based on the Shapiro–Wilk and Kolmogorov–Smirnov tests (p < 0.05). The results showed that the average body weight of Bali cattle in 1445 H was 337.74 ± 55.13 kg with a CV of 16.32%, while in 1446 H the average body weight was 331.79 ± 47.96 kg with a CV of 14.46%. CV values below 20% indicated that cattle body weights were relatively homogeneous, with higher uniformity observed in 1446 H. The Mann–Whitney U test yielded a significance value of p = 0.362 (p > 0.05), indicating that there was no significant difference in Bali cattle body weight between the two years. It can be concluded that the body weight of Bali cattle slaughtered for Eid al-Adha in Bali was relatively stable across years, reflecting consistent management practices and the genetic contribution of Bali cattle in maintaining stable body weight performance.